Enjoying tranquility — Development of ground vegetation after cessation of management in forests on loamy soils in Flanders (Belgium). Issue 3 (21st July 2021) - Vandekerkhove, Kris; Thomaes, Arno; De Keersmaeker, Luc; Van de Kerckhove, Peter; Onkelinx, Thierry; Van Calster, Hans; Verheyen, Kris
Abstract: Questions: Managed forests often show a more homogeneous age structure compared to unmanaged forests, but also a higher share and frequency of canopy and soil disturbances due to harvest operations. Here, we investigate what happens when non‐intervention is introduced in formerly managed forests: Was there a significant decrease in vascular plant species richness? Which species were particularly affected? Are there non‐random shifts in species composition? Were typical shade‐tolerant forest species also jeopardized due to prolonged deep shade? Location: Four recently installed strict reserves in Atlantic to Sub‐Atlantic lowland oak and beech forests on fertile loess soils east and southwest of Brussels (Belgium). Methods: We compared vegetation relevés in permanent plots (183 plots of 16 m × 16 m) with a 10‐year interval. Total species richness per site was derived from rarefaction curves; significance of differences in species richness and composition at plot level were tested using paired t tests and Wilcoxon signed rank tests. Non‐metric multidimensional scaling analysis (NMDS) was used to check for non‐random shifts in species composition. Results: We registered significant declines in species richness both at reserve and plot level. This decline was not random, but strongly dependent on ecological traits and strategies, with strong declines in light‐demanding gap phase‐associated species like Lonicera periclymenum and Deschampsia cespitosa, and species requiring soil disturbance, such as Juncus effusus and Carex sylvatica . Shade‐tolerant mesic species like Anemone nemorosa and Allium ursinum clearly increased in frequency and cover, despite strong declines in previous decades. Conclusion: The effect of lower disturbance frequency leading to continued closed canopy, against a background of reduced atmospheric deposition, induces the development of a ground vegetation with lower species richness, due to decrease of species related to disturbance, but with higher dominance and cover of characteristic species of mesic lowland oak and beech forests. Abstract : Vegetation changes were investigated in fourformerly managed strict reserves inBelgium, using permanent plots resurveyed after 10 years. We registered declines in species richness, but shade‐tolerant species and vernal geophytes (like this Anemone nemorosa ) clearly increased, resulting in a less speciesrich vegetation, but with higher dominance of characteristic species of mesiclowland forests.